2019
DOI: 10.1208/s12248-018-0262-1
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib N-Oxide Is an Inhibitor of Human Hepatic CYP3A4

Abstract: The multi-kinase inhibitor sorafenib (SOR) is clinically important in the treatment of hepatocellular and renal cancers and undergoes CYP3A4-dependent oxidation in liver to the pharmacologically active N-oxide metabolite (SNO). There have been reports that kinase inhibitors such as SOR may precipitate pharmacokinetic interactions with coadministered drugs that compete for CYP3A4-mediated biotransformation, but these occur non-uniformly in patients. Clinical evidence also indicates that SNO accumulates in serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…Since SR_G plays a crucial role in the enterohepatic circulation of sorafenib [ 5 ], it is more likely that the increased SR_NO/sorafenib exposure ratios are a result of rapid intestinal transit, which shortens the time for SR_G transformation to sorafenib and sorafenib re-absorption, than a result of CYP3A4-mediated DDIs. However, sorafenib itself has shown CYP3A4-inhibitory properties in an in vitro study [ 37 , 40 ], and therefore, metformin could promote the CTP3A4-mediated pathway by alleviating the obstacles (by sorafenib concentration reduction). However, this metabolization hypothesis seems to be less established, especially considering that the direct impact of metformin on CYP3A4 activity remains largely unknown [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since SR_G plays a crucial role in the enterohepatic circulation of sorafenib [ 5 ], it is more likely that the increased SR_NO/sorafenib exposure ratios are a result of rapid intestinal transit, which shortens the time for SR_G transformation to sorafenib and sorafenib re-absorption, than a result of CYP3A4-mediated DDIs. However, sorafenib itself has shown CYP3A4-inhibitory properties in an in vitro study [ 37 , 40 ], and therefore, metformin could promote the CTP3A4-mediated pathway by alleviating the obstacles (by sorafenib concentration reduction). However, this metabolization hypothesis seems to be less established, especially considering that the direct impact of metformin on CYP3A4 activity remains largely unknown [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional sorafenib N-oxide exposure (Table 2) is probably a consequence of increased exposure to sorafenib. Considering the fact that both sorafenib and SR_NO exhibit inhibitory effects on CYP3A4 [37], and since atorvastatin itself is its substrate, the induction of CYP3A4 is highly unlikely. Since SR_NO exhibits pharmacological activity, the risk of toxicity is further enhanced.…”
Section: The Influence Of Atorvastatin On the Pharmacokinetics Of Sormentioning
confidence: 99%
See 1 more Smart Citation
“…activity (8). We found recently that CYPs 3A4 and 2D6 were inhibited more effectively by SNO than SOR because the binding of SNO within the active centers of the enzymes was more effective (10,11). These findings suggest that patients that produce more SNO may be at greater risk of pharmacokinetic DDIs.…”
Section: Sno Formation Varies Between Patients Due To Individual Differences In Cyp3a4mentioning
confidence: 91%
“…1), are 3.3 and 5.4 Å from the Fe atom of the heme. Ghassabian et al (2019) similarly reported that the distance of the site of N-oxidation from the heme (Fe atom) was 3.3 Å when sorafenib was docked in another unliganded CYP3A4 structure (pdb code 1TQN). Use of sorafenib as the template for ligand superposition predicted the SOM of 22 of the 31 data set molecules (prediction accuracy of ;71%) ( Table 6).…”
Section: Cyp3a4-mediated Som Prediction Of Protein Kinase Inhibitorsmentioning
confidence: 95%